2010
DOI: 10.1080/87568225.2010.486291
|View full text |Cite
|
Sign up to set email alerts
|

Eating Disorders as Coping Mechanisms

Abstract: Journal of College Student PsychotherapyPublication details, including instructions for authors and subscription information:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…The home environment has an important influence on the development of EDs and/or DEBs (Jacobi et al 2004); in a systematic review of the causes of EDs, Polivy and Herman (2002) identify negative family environments and lack of familial support during early childhood as major risk factors for EDs. EDs are often understood as coping mechanisms for the perceived lack of control or support in the home environment (Polivy and Herman 2002;Wagener and Much 2010). Many societies emphasize culturally idealized thinness, and individuals with EDs are aware of the importance of this ideal, internalize it, and perceive pressure from the media and their peers to be thin (Levine and Murnen 2009).…”
Section: Eating Disorders and Disordered Eating Behaviorsmentioning
confidence: 99%
“…The home environment has an important influence on the development of EDs and/or DEBs (Jacobi et al 2004); in a systematic review of the causes of EDs, Polivy and Herman (2002) identify negative family environments and lack of familial support during early childhood as major risk factors for EDs. EDs are often understood as coping mechanisms for the perceived lack of control or support in the home environment (Polivy and Herman 2002;Wagener and Much 2010). Many societies emphasize culturally idealized thinness, and individuals with EDs are aware of the importance of this ideal, internalize it, and perceive pressure from the media and their peers to be thin (Levine and Murnen 2009).…”
Section: Eating Disorders and Disordered Eating Behaviorsmentioning
confidence: 99%
“…These are narratives that have constructed alternative understandings of "anorexia" (Krug et al, 2013;Marzola et al, 2015;Racine & Wildes, 2013;Rance et al, 2017;Tierney & Fox, 2010;Wildes et al, 2010;Williams & Reid, 2010). In this context, it has been reported that negative, dominant, personal, discourses have adversely influenced the lives and living experiences of persons (MacNeil et al, 2012;Morris & Twaddle, 2007;Wagener & Much, 2010). In addition, persons have reported that their lived experiences with their relationship with "anorexia" have shown that "anorexic" behavior, feelings and thoughts, were coping mechanisms, or forms of resistance (e.g., Faija et al, 2017;Morris & Twaddle, 2007;Williams & Reid, 2012;Wagener & Much, 2010).…”
Section: Psychological Thoughtmentioning
confidence: 99%
“…These coping mechanisms provide ways of protection, defence, safety and resistance against stress, future challenges and anxieties, conflicts, unexpected and undesirable changes in the lives of those persons (Botha, 2014(Botha, , 2019e.g., MacNeil et al, 2012;Marzola et al, 2015;Schmidt & Treasure, 2006;Wagener & Much, 2010). The participants in the study by Williams & Reid (2012) indicated that anorexia "was their only way of coping because they had not learned other coping strategies; thus, they depended on their disorder and felt that they 'needed' it" as "their disorder enabled them to 'survive' their unpleasant experiences" (p. 804).…”
Section: Psychological Thoughtmentioning
confidence: 99%
See 1 more Smart Citation
“…Family modeling is another pathway that is related to high risk behaviors among women (Kluck, 2008). Moreover, individuals use unhealthy behaviors as coping mechanism in time of difficulties (Dube, Anda, Felitti, Edwards, & Croft, 2002;Wagener & Much, 2010).…”
Section: Aggressive Behavior Percentagementioning
confidence: 99%